Influence of Duration period of Fattening Average Daily Gain and Fatty Acids Composition of Brahman Cross Cattle - Soebagyo, Yohannes; Ngadiyono, Nono; Bachrudin, Z (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2000)
One hundred and eighty castrated male of Brahman Cross cattle ,2 to 2.50 years old with initial body weight of 341.50Â± 18.20 kg, were used in this research to study the effect of duration period of fattening on average daily gain and fatty acids composition of meat. They were grouped randomly into three : 2 months ( group A),3 months (group B) and 4 months ( group C) of fattening of each group consisted of three pens of 20 heads respectively. The diet was composed of 15 percent of king grass ,80 percent of concentrate and 5 percent of waste product of fermented beer and given ad libitum as total mixed ration. Feed intake was controlled every day, were asÂ weighting was done monthly. Meat samples for analyses of fatty acids composition and were taken from Longisimus dorsi and collected from 6 cattle as a replication for each treatment. All data collected were analysed by analysis of variance using completely Randomized Design (CRD). Treatment were compared using Least Significant Difference (LSD).ADG in group C (0,75 kg ) was significantly higher (P < 0,05) than in group A (0,08 kg ) and B (0,82 kg ) and three was not difference between A and B . Meat fat content and percentage of saturated fatty acids were significantly higher (P< 0,05 ) in group C (12.53 percent ; 43.16 percent ) than in group A (5.31 percent ; 38.43 percent ) and in group B (5,27 percent ; 38.05 percent ). On the contrary, the percentage of unsaturated fatty acids was significantly (P < 0,05) lower (C: 56.76 percent ) than other group ( A : 61.70 percent and B : 61.95 percent). (Animal Production 2(1): 33-39 (2000)Key Word : average daily again , fatty acids composition, Brahman Cross cattle.